Monitoring of urban and rural basins: water quality of Mourão basin - F. H. Passig; S. B. Lima; K. Q. Carvalho; M. C. R. Halmeman; P. C. Souza; L. K. Gusmão (Brazilian Journal of Biology)
The Mourão River basin is located on the central western region of the Paraná State – Brazil, between coordinates 23º 44’ - 24º 25 South latitude and 52º 12’ - 52º 30’ West longitude, between 270 and 820 m above sea level, and 1,648.21 km2 drainage area. Water quality was evaluated by monitoring physical, chemical and microbiological parameters. Monthly samplings were performed for a year at five sites in the basin for analysis of: pH, temperature, dissolved oxygen, biochemical oxygen demand, total nitrogen, ammoniacal nitrogen, nitrite, nitrate, total phosphorus, turbidity, total solids, volatile solids and fecal coliforms. The results of the evaluated parameters showed higher values than the limits set by CONAMA Resolution 357 from 2005 for Class 2 in some samples. The Water Quality Index (WQI) indicated that 72% of samples had average quality and 28% had good quality for the Mourão River basin. Higher values of WQI were observed after rainfall period with median of 75 compared to the dry period with median of 62. The source of the Mourão River is contaminated with fecal coliforms, evidencing the real need to treat sewage in rural areas.